PERAN E-LEARNING DALAM PROSES PEMBELAJARAN MAHASISWA UNIVERSITAS ESA UNGGUL TANGERANG - Grandis Priya Reagan; Eka Pajri Firmansyah (Cahaya Ilmu Bangsa, 2025)
Research shows that e-learning at Esa Unggul University Tangerang significantly helps learning, especially during the pandemic. The system allows students to learn anytime and anywhere, increasing independence and digital skills. Despite obstacles such as technical issues and lack of technology skills among senior lecturers, e-learning facilitates the exchange of information, access to materials, and interaction between students and lecturers through features such as quizzes, forums, and assignments. The university also provides training to help with adaptation. Based on the theory of Social Construction of Reality by Berger and Luckmann, social interactions in e-learning form a